2002
DOI: 10.1016/s0896-6273(02)00752-3
|View full text |Cite
|
Sign up to set email alerts
|

Raf and Akt Mediate Distinct Aspects of Sensory Axon Growth

Abstract: Nerve growth factor (NGF) induces dramatic axon growth from responsive embryonic peripheral neurons. However, the roles of the various NGF-triggered signaling cascades in determining specific axon morphological features remain unknown. Here, we transfected activated and inhibitory mutants of Trk effectors into sensory neurons lacking the proapoptotic protein Bax. This allowed axon growth to be studied in the absence of NGF, enabling us to observe the contributions of individual signaling mediators. While Ras w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
270
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(305 citation statements)
references
References 79 publications
30
270
2
3
Order By: Relevance
“…Akt also has been demonstrated to regulate axonal growth. In culture, Akt expression modifies axon branching of peripheral sensory neurons (13), and, in vivo, it regulates the rate of regeneration of peripheral motor nerves after axotomy (14). We demonstrate here in the central nervous system that Akt also regulates axon sprouting in both adult and aged animals, either in the presence or absence of injury.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Akt also has been demonstrated to regulate axonal growth. In culture, Akt expression modifies axon branching of peripheral sensory neurons (13), and, in vivo, it regulates the rate of regeneration of peripheral motor nerves after axotomy (14). We demonstrate here in the central nervous system that Akt also regulates axon sprouting in both adult and aged animals, either in the presence or absence of injury.…”
Section: Discussionmentioning
confidence: 68%
“…Akt signaling mediates two principal cellular responses to neurotrophic factors. It maintains viability through antiapoptotic effects [reviewed in Brunet et al (12)], and it mediates effects on axonal caliber, branching (13), and regeneration (14). Almost all of these observations, however, have been made in vitro, and it has not been known whether they generalize to the in vivo context, particularly in the central nervous system.…”
mentioning
confidence: 99%
“…In Bcl-2-overexpressing RGCs, pharmacologic inhibition of either MAPK or PI3K partially reduce axon outgrowth, but inhibiting both together is necessary to block axon elongation altogether (Goldberg et al 2002a). In Bax-deficient DRG neurons exposed to NGF, blocking raf, PI3K, or the PI3K-activated kinase Akt decreases axon elongation, but stimulating the raf-MAPK cascade induces axon elongation, whereas stimulating PI3K or Akt increased axon thickness and branching (Markus et al 2002). Therefore the data from various investigators continue to be somewhat contradictory and may reflect differing signaling requirements in different neurons isolated at different ages.…”
Section: How Do Extracellular Signals Induce Axon Elongation?mentioning
confidence: 99%
“…It has long been hypothesized that reactivation of developmental growth mechanisms might help to achieve axon regeneration in the injured adult nervous system (Filbin, 2006). The role of MAP kinases in axon growth signaling has been much studied and discussed (Markus et al, 2002;Hanz and Fainzilber, 2006;Agthong et al, 2009;Hollis et al, 2009). However, depending on the model systems used, the outcomes have been controversial or even contradictory (Pernet et al, 2005;Sapieha et al, 2006;Hollis et al, 2009).…”
mentioning
confidence: 99%
“…However, depending on the model systems used, the outcomes have been controversial or even contradictory (Pernet et al, 2005;Sapieha et al, 2006;Hollis et al, 2009). We have shown that RAF-MEK signaling robustly promotes axon growth in primary sensory neurons in vitro (Markus et al, 2002). In vivo, conditional gene targeting studies have shown that RAF signaling is necessary for developing sensory neurons to arborize in their target fields in the skin (Zhong et al, 2007).…”
mentioning
confidence: 99%